MUSEUM OF VERNACULAR ARCHITECTURE OF WESTERN SERBIA - Representative curtilages of the area surrounding middle course of the river Drina and Podgorina - Kuzović, Duško (Economics of Agriculture, 2017)
The Museum of vernacular architecture of western Serbia will consist of four representative curtilages and four different entities. This paper presents two curtilages representing the area of the middle course of the river Drina, and the area of Podgorina. The buildings typically located in the curtilage are: house, magaza (plural: magaze) - food storage shed, kačara (plural: kačare) - cask shed, vajat (plural: vajati) - cottage for newly-wed couples, granary, maize granary, bread oven, ox cart shed. The buildings are presented by drawings and photographs. The text describes curtilage organization; this comprises buildings position, organization and structure.